2021
DOI: 10.1186/s40510-021-00369-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 12 weeks of mechanical vibration on root resorption: a micro-CT study

Abstract: Objective The aim was to investigate the effect of mechanical vibration on root resorption with or without orthodontic force application. Material and methods Twenty patients who required maxillary premolar extractions as part of orthodontic treatment were randomly divided into two groups of 10: no-force group and force group. Using a split-mouth procedure, each patient’s maxillary first premolar teeth were randomly assigned as either vibration or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
4
0
2
Order By: Relevance
“…Root volume measurements were used to quantify root resorption, by comparing the remaining root volume with the control group. Numerous previous studies used micro-CT to evaluate root resorption [28,29]. The root volume did not change considerably in response to force exertion or vibration application in this present study.…”
Section: Discussionsupporting
confidence: 43%
“…Root volume measurements were used to quantify root resorption, by comparing the remaining root volume with the control group. Numerous previous studies used micro-CT to evaluate root resorption [28,29]. The root volume did not change considerably in response to force exertion or vibration application in this present study.…”
Section: Discussionsupporting
confidence: 43%
“…Nine articles were selected for data extraction ( 13 , 129 , 134 , 135 , 130 , 36 , 131 , 132 , 133 ). All articles were published between 1986 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…However, only total Root Resorption values reached statistical significance. It was found that the PzC procedure resulted in a 44% average increase in RR compared with the control side [ 14 ].…”
Section: Discussionmentioning
confidence: 99%